External Cueing Influences Drop Jump Performance in Trained Young Soccer Players. Issue 6 (June 2021) - Oliver, Jon L.; Barillas, Saldiam R.; Lloyd, Rhodri S.; Moore, Isabel; Pedley, Jason
Abstract : Abstract: Oliver, JL, Barillas, SR, Lloyd, RS, Moore, I, and Pedley, J. External cueing influences drop jump performance in trained young soccer players. J Strength Cond Res 35(6): 1700–1706, 2021—Drop jump (DJ) characteristics provide insight on power production and injury risk. The purpose of this study was to investigate the effect of external cueing on DJ characteristics in young male soccer players. Fourteen academy soccer players performed DJs with 4 different conditions, control (CONT), contact cue (CC), height cue (HC), and quiet cue (QC). Performance measures were reactive strength index (RSI), jump height, ground contact time (GCT), and take-off impulse, with injury risk reflected by impact peak, impact timing, and landing impulse. Contact cue showed a very large significant reduction in GCT (effect size [ES] > 2.0, p < 0.05), and moderate to large increase in RSI, landing impulse, and push-off impulse (ES 0.70–1.55, p < 0.05) compared with all other conditions. Contact cue also moderately increased impact peak when compared with HC and QC (ES ≥ 0.78, p < 0.05). Height cue led to a significant increase in jump height that was moderately greater than other external cues (ES ≥ 0.87, p < 0.05), but with only a small nonsignificant increase compared (ES 0.54, p > 0.05) with CONT. The data showed that all cues provided a specific response; CC reduced GCT and increased RSI, HC increased jump height, and QC reduced outcomes associated with injury risk. Height cue may be advantageous for young soccer players with a low training age because it shows a small to moderate increase in jump height without increasing injury risk. Young players may need to be safely progressed to be able to use a CC to facilitate high reactive strength without being exposed to undue injury risk.